2018
DOI: 10.1021/jacs.8b02931
|View full text |Cite
|
Sign up to set email alerts
|

Template-Free Synthesis of Periodic Three-Dimensional PbSe Nanostructures via Photoelectrodeposition

Abstract: Highly periodic, geometrically directed, anisotropic Se–Pb films have been synthesized at room temperature from an isotropic aqueous solution without the use of physical templates by photoelectrodeposition using a series of discrete input illumination polarizations and wavelengths from an unstructured, uncorrelated, incoherent light source. Dark growth did not generate deposits with substantial long-range order, but growth using unpolarized illumination resulted in an ordered, nanoscale, mesh-type morphology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…In previous studies, we have successfully demonstrated simulated phototropic growth of Se−Te, PbSe, and CdSe using an optical-based, two-step, iterative model. 1,7,8 Additional details for this modeling process are provided in the Methods section. Figure 6 , the simulated growths exhibited improved fidelity and straighter features on template substrates than on unpatterned substrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we have successfully demonstrated simulated phototropic growth of Se−Te, PbSe, and CdSe using an optical-based, two-step, iterative model. 1,7,8 Additional details for this modeling process are provided in the Methods section. Figure 6 , the simulated growths exhibited improved fidelity and straighter features on template substrates than on unpatterned substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Phototropic growth of these semiconducting materials occurs via a single-step process that does not utilize chemical or physical templating. Highly anisotropic lamellae resulting from inorganic phototropic growth under uniform, polarized optical excitation conditions have been observed for Se−Te, 1−6 PbSe, 7 and CdSe. 8 Optical modeling and simulations of the inorganic phototropic growth process have demonstrated that the high-aspectratio lamellae formed in phototropically grown films result from a feedback loop initiated by light scattering from an initial collection of nucleated particles that are isotropically distributed on the substrate.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Se–Te alloys are semiconductors with energy-band gaps ( E g ) that are between those of Se ( E g ≈ 1.85 eV) and Te ( E g ≈ 0.33 eV), depending on the ratio of Se to Te as well as the crystallinity of the material. Phototropic growth with consequent optically based nanoscale morphology control has also been observed for PbSe films, which suggests that the phenomenon may be general for semiconductors with short minority-carrier diffusion lengths . A model that combines full-wave optical simulations with weighted Monte Carlo mass addition accurately reproduces the average pattern period and morphology for phototropic Se–Te structures grown under multiple and complex optical inputs. ,, …”
Section: Matched-illumination Growth Conditionsmentioning
confidence: 99%
“…3−6 Phototropic growth with consequent optically based nanoscale morphology control has also been observed for PbSe films, which suggests that the phenomenon may be general for semiconductors with short minority-carrier diffusion lengths. 7 A model that combines fullwave optical simulations with weighted Monte Carlo mass addition accurately reproduces the average pattern period and morphology for phototropic Se−Te structures grown under multiple and complex optical inputs. 2,8,9 Se−Te photoelectrodeposits exhibit phototropic growth on a variety of substrates including Au, highly oriented pyrolytic graphite, n + -Si(111), and p-Si(100).…”
mentioning
confidence: 99%